Dizziness-related disability following mild–moderate traumatic brain injury. (19th September 2017) - Kleffelgaard, I.; Langhammer, B.; Hellstrom, T.; Sandhaug, M.; Tamber, A. L.; Soberg, H. L.
ABSTRACT: Objective : To investigate the associations between dizziness-related disability after mild- moderate Traumatic Brain Injury (TBI) and personal factors, injury-related factors and post-injury functioning using the International Classification of Functioning, Disability and Health (ICF) as a framework. Methods : Baseline assessments for a Randomised Controlled Trial (RCT) were obtained for 65 patients (mean age 39.2 years; SD 12.9 years; 70.8% women) who had dizziness and reduced balance 2–6 months after injury. The severity of the brain injury, physical and psychological self-reported symptoms and results from the performance based tests were used as independent variables. The main outcome measure (dependent variable) was the Dizziness Handicap Inventory (DHI). Results : Multivariate analyses showed that, the dizziness-related disability was predicted by pre-injury comorbidities ( p ≤ 0.05) and was associated with self-reported vertigo symptoms ( p < 0.001), reduced performance-based balance ( p ≤ 0.05) and psychological distress ( p ≤ 0.05). These factors accounted for 62% of the variance in DHI. Conclusion : Dizziness and balance problems after mild-moderate TBI appear to be complex biopsychosocial phenomena. Assessments linked to the ICF domains of functioning might contribute to a broader understanding of the needs of these patients. Further, prospective clinical studies with non-dizzy control groups are needed to investigate dizziness-related disability after TBI.